Prevalence of Bruxism and Its Association with Stress among Dental Students: A Questionnaire-Based Cross-Sectional Study - Durga Prasad Naik, Ketavatu; Gortha, Prasanthi; Varma, Madhu; Kumar, Mohan; Koruprolu, Rama Laxmi; Rameswarapu, Mounika (Journal of Dentistry Indonesia, 2025)
Objective: Bruxism has been described as a parafunction associated with a multifactorial etiology, but primarily as a psychological factor. This study determined the prevalence of bruxism among dental students and explored the potential contributing factors. Methods: A cross-sectional self-administered questionnaire survey was conducted among dental students across various academic years. The prevalence of bruxism (awake and during sleep) was assessed along with stress levels, lifestyle factors, and demographic variables. Statistical analyses were performed using the chi-square test and multivariate logistic regression. Results: The prevalence of bruxism was significantly associated with stress and academic workload. Most participants exhibited moderate to severe stress. Of these, most reported symptoms of bruxism. However, formal diagnoses and treatment-seeking behaviors were low. Conclusions: Bruxism is prevalent among dental students and may be associated with academic stress. Implementing preventive strategies, such as stress management programs and awareness campaigns, could help reduce its impact.